Studies of pilocarpine:carbomer intermolecular interactions - Zoppi, Ariana (2012)
The interactions between pilocarpine (PIL) and the anionic polyelectrolyte carbomer (CBR) were investigated. The effects of the chemical interactions on the chemical stability of the drug also were evaluated. The binary system was characterized by nuclear magnetic resonance techniques, Fourier-transform infrared spectroscopy (FT-IR), X-ray powder diffraction, scanning electron microscopy (SEM) and thermal analysis. The experiments showed that the complex, prepared by freeze-drying, is a solid amorphous form different from its precursors, thereby offering an interesting alternative for the preparation of extended release matrices. The solution stability of PIL was studied at pH 7 and 8, at 70 ◦C. The PIL solution stability was evaluated alone and in the presence of CBR. Results indicated that the drug in the presence of the polymer is 3.3 and 3.5 times more stable, at pH 7 and pH 8, respectively, than the drug without CBR. The activation energy and the frequency factor, according to Arrhenius plot, were estimated to be 13.9 ±0.4 and 14.8 ± 0.5 kcal mol-1, and 6.1 ± 0.3 and 7.6 ± 0.3, with and without the polymer, respectively.